KONSEP PENDIDIKAN ISLAM DALAM KITAB ADAB ALMU’ALLIMIN KARYA IBN SUHNUN - Salman - (STAI Tuanku Tambusai, 2020)
This thesis discusses the concept of Islamic education in the book Adab al-Mu'allimin. The Book of Adab al-Mu'allimin is a very important book as a source of reference by every teacher, especially for those who will be prospective teachers. IbnSahnun plays an important role in initiating education in Islam, so he is known by the educational leaders of Muslims. His work is about educating and combining the Tarbiyah School and the Fiqh School.In other words, it includes religious education, moral education, intellectual education, vocational education, physical education and social education. The competencies that an Islamic elementary educator should have include religious pedagogical competence, religious social competence, religious professional competence, religious moral competence, religious competence, and religious emotional competence.Theresearch model used is a qualitative model with qualitative descriptive approach, where descriptive research is not intended to test a particular hypothesis but describes